Development of spectrophotometrıc determınatıon method for Au(III) whıch ıs used Ag(I) [Au(III) için Ag(I) kullanılarak spektrofotometrik bir tayin yönteminin geliştirilmesi] - (:unkn) unknown (Marmara University, 2017)
In this research, m- and p- phenylenediamine which is used as the therapeutic Ag(I) and Au(III) in reaction to the metal is intended to develop a potentiometric and analyzed spectrophotometric method. The results of the reactions between Ag(I) and Au(III) and m- and p-phenylenediamine mixtures it was found out that, there is an oxidation by means of complexation. And as a result of oxidation, a diazo compound occured from amines and Ag(I) was reducted to elementel form, Au(III) was reducted to Au(I). Also the formation conditions of the reactions of these metals with amines were investigated, the pH range that the reactions takes place, time needed for the formation of the reactions and the mol ratios needed for the complete reaction of the metals with amines. Mole ratios were determined as follows: Ag(I) / (m+p)phenylenediamine= 1; Au(III) / (m+p)phenylenediamine= 1/2. © 2017, Marmara University. All rights reserved.
Keywords: Ag(I) and Au(III); M- ve p-phenylenediamine; Potentiometer; Spectrophotometer